2017
DOI: 10.22161/ijeab/2.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Productive and Reproductive Traits of Sheep Fed Acacia saligna Leaves-Based Diets

Abstract: Abstract-Investigating effects of partial (50%) or total (100%) substitution of clover hay by tannins-rich plant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The hematological values obtained in the current study were within the expected ranges (Beigh et al, 2018) 2017) also observed reduced TP with partial substitution of clover hay by acacia sp. The current study shows no signi cant effect of diet on TP across all the dietary treatments, however, numerically lambs fed on a diet containing Acacia leaves (AMSAL) had higher serum TP and more comparable to control diet-fed lambs, this could be enhanced by the interaction of Acacia leaves and ammoniated stover as observed in as study by Sallam et al (2017).…”
Section: Discussionsupporting
confidence: 40%
“…The hematological values obtained in the current study were within the expected ranges (Beigh et al, 2018) 2017) also observed reduced TP with partial substitution of clover hay by acacia sp. The current study shows no signi cant effect of diet on TP across all the dietary treatments, however, numerically lambs fed on a diet containing Acacia leaves (AMSAL) had higher serum TP and more comparable to control diet-fed lambs, this could be enhanced by the interaction of Acacia leaves and ammoniated stover as observed in as study by Sallam et al (2017).…”
Section: Discussionsupporting
confidence: 40%